PEMBERDAYAAN MASYARAKAT MELALUI EKONOMI KREATIF AKAR WANGI DI GARUT, JAWA BARAT: PEMBERDAYAAN MASYARAKAT MELALUI EKONOMI KREATIF AKAR WANGI DI GARUT, JAWA BARAT - Santi Susanti; Pandu Watu Alam (Jurnal Kajian Budaya dan Humaniora, 2024)
Generally, the creative economy industry starts from small and medium enterprises (SMEs) that grow to become large. The existence of the internet, which was born from the development of information technology, makes it easier for creative SME entrepreneurs to market their products and conduct transactions with consumers. Various online media are utilized so that potential customers are familiar with the products offered, and can directly order without having to visit the store directly. This study aims to reveal the empowerment of local wisdom-based creative economic potential through e-commerce. The research was conducted in Garut with the object of research is Zocha Graha Kriya, Garut Handicraft Center, which empowers the potential of local resources in the form of vetiver, becoming souvenirs for tourists visiting Garut. Using a qualitative research method with a case study approach, this research reveals that Zocha Graha Kriya has succeeded in empowering vetiver as a local potential for the creative economy into works that have aesthetic value and are useful. The potential of local human resources was also successfully empowered so that the results of the local economic potential did not leave Garut. This strategy succeeded in optimizing the utilization of the local potential of the vetiver creative industry into an SME industry managed from-by-and for Garut.